2018
DOI: 10.3233/wor-172664
|View full text |Cite
|
Sign up to set email alerts
|

The impact of occupational splash, sharps and needlestick injuries (SSNIs) on the quality of life of healthcare workers in a Kenyan university hospital

Abstract: SSNIs clearly impact on healthcare workers quality of life. Hospital management should ensure measures are taken to reduce SSNIs and provide appropriate personal protection equipment. For staff experiencing an SSNI, psychological wellbeing should be assessed and appropriate expert help provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Healthcare workers are at greater risk of occupational exposure to splashes, sharps, and needlestick injuries (SSNIs) [ 1 ]. Since, splashing of blood and body secretion has not been mentioned in the majority of studies and their focus was on needlestick and sharp injuries in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare workers are at greater risk of occupational exposure to splashes, sharps, and needlestick injuries (SSNIs) [ 1 ]. Since, splashing of blood and body secretion has not been mentioned in the majority of studies and their focus was on needlestick and sharp injuries in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The studies explored in this review suggest that medical students need psychological support following a sharps injury. Healthcare workers sustaining a sharps injury should be assessed and appropriate expert help provided for their psychological wellbeing (Ongete and Duffy, 2018). Owing to the psychological impact that sharps injuries can have on healthcare workers, Wu et al (2014) suggested that follow-up interventions should include psychosocial support, but the evidence suggests that this is not always happening.…”
Section: Discussionmentioning
confidence: 99%
“…One research published by Ongete and Duffy early this year [10] revealed a lot. The cross sectional descriptive study conducted in a Kenyan University Teaching and Referral Hospital sampled at risk cadre of staff including doctors, nurses, housekeeping staff, phlebotomists, dentists amongst others n= 416, out which 192(46.2%) had experienced SSNIs.…”
Section: Quality Of Life Impactmentioning
confidence: 99%